Efeito do tipo de parto vaginal sobre a perda hemática em mulheres - Armellini, Cláudia Junqueira [UNIFESP] (2010)
Objectives: analyze the prevalence of anemia during pregnancy and its incidence on the postpartum period, as well as the effect of vaginal birth (spontaneous with episiotomy, spontaneous without episiotomy, and forceps with epsiotomy) on the variation of hemoglobin and hematocrit levels after birth. Method: It is an epidemiological, prospective and observational study, developed in two maternities in the city of São Paulo/Brazil, from June 15, 2008 to October 16, 2009. The sample was of 328 primiparous women, who gave birth at term to a single live baby in cephalic presentation, and had at least three prenatal visits registered on the pregnancy card. The data collection was done in three phases: admission, hospital discharge and puerperal evaluation; through a semi-structured form and the collection of venous blood samples. To diagnose anemia, hemoglobin levels were measured; to analyze the effect of the birth procedure on the blood loss, hemoglobin levels and hematocrit concentration were measured. In the data analysis, Student´s t-test, Chi-square test, and Proportion Analysis test were used, according to each variable group studied. The confidence interval was of 95%. Results: The prevalence of anemia was of 4% at admission, with an incidence of 67.4% at hospital discharge, and 5.8% at puerperal evaluation. Forceps with episiotomy deliveries have caused a significant higher hemoglobin decrease between the admission and hospital discharge phases, when compared to spontaneous births with or without episiotomy. Spontaneous deliveries with episiotomy led to a significant higher hemoglobin value reduction between the phases of admission and hospital discharge, when compared to spontaneous deliveries without episiotomy. Spontaneous deliveries without episiotomy resulted in a significantly higher hemoglobin raise between the phases of puerperal evaluation and hospital discharge, when compared to forceps with episiotomy and spontaneous deliveries with episiotomy. Conclusion: Anemia percentage has varied, raising between the admission and hospital discharge phases; and dropping between hospital discharge and puerperal evaluation. Forceps with episiotomy deliveries and spontaneous deliveries with episiotomy, led to higher blood loss, when compared to spontaneous deliveries without episiotomy. Therefore, it is relevant to evaluate blood loss due to birth, considering the early diagnose and treatment of maternal morbidity, especially, of anemia.